Exploring Perceived Human Resources Factors Influencing the Performance of Grade 12 Accounting Learners in North West Secondary Schools in South Africa - Lilian Ifunanya Nwosu; Martha Matashu (Research in Social Sciences and Technology, 2022)
This study explored the perceived human resources factors influencing the performance of accounting learners in North West secondary schools in South Africa. Despite the significant role that secondary school accounting education is perceived to play in shaping the development of accounting professionals, few studies have focused on investigating the effect of human resources on accounting learners’ performance in secondary school. The study sought to understand the human resource factors influencing the performance of accounting learners in North West secondary schools in South Africa. The study’s findings may assist the school management to improve human resource utilisation towards the achievement of a better accounting learners’ performance. To address the gap in the literature, a mixed method sequential explanatory study was conducted in North West districts with 183 School Management Teams and 61 educators. The sequential explanatory study aimed to explore the perceived human resources factors influencing the performance of Grade 12 Accounting learners in secondary schools in the North West Province, South Africa. The findings from the quantitative phase showed that human resource factors such as pedagogical subject content knowledge and skills held by the educator are perceived to influence learner performance. In the second phase, the qualitative approach validated and explained the various human resource factors that influence accounting learners’ performance in North West secondary schools in South Africa. School management should ensure that they employ adequate accounting learners to teach accounting in schools. This is so because accounting requires a pedagogical content knowledge and skills in teaching and learning. In conclusion, it is recommended that schools interested in improving learner performance should identify and address context-specific perceived human resources factors that influence learner performance within their schools.This study explored the perceived human resources factors influencing the performance of accounting learners in North West secondary schools in South Africa. Despite the significant role that secondary school accounting education is perceived to play in shaping the development of accounting professionals, few studies have focused on investigating the effect of human resources on accounting learners’ performance in secondary school. The study sought to understand the human resource factors influencing the performance of accounting learners in North West secondary schools in South Africa. The study’s findings may assist the school management to improve human resource utilisation towards the achievement of a better accounting learners’ performance. To address the gap in the literature, a mixed method sequential explanatory study was conducted in North West districts with 183 School Management Teams and 61 educators. The sequential explanatory study aimed to explore the perceived human resources factors influencing the performance of Grade 12 Accounting learners in secondary schools in the North West Province, South Africa. The findings from the quantitative phase showed that human resource factors such as pedagogical subject content knowledge and skills held by the educator are perceived to influence learner performance. In the second phase, the qualitative approach validated and explained the various human resource factors that influence accounting learners’ performance in North West secondary schools in South Africa. School management should ensure that they employ adequate accounting learners to teach accounting in schools. This is so because accounting requires a pedagogical content knowledge and skills in teaching and learning. In conclusion, it is recommended that schools interested in improving learner performance should identify and address context-specific perceived human resources factors that influence learner performance within their schools.